Modification of the existing maximum residue level for tefluthrin in carrots. (10th October 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta France S.A.S. submitted a request to the competent national authority in France to modify the existing maximum residue level (MRL) for the active substance tefluthrin in carrots. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for carrots. Adequate analytical methods for enforcement are available to control the residues of tefluthrin in carrots at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of tefluthrin according to the reported agricultural practices is unlikely to present a risk to consumer health. The reliable end points, appropriate for use in regulatory risk assessment are presented.